The timely content of critical theory: are there arguments of epistemological innovation? - Marinopoulou, Anastasia (The Greek Review of Social Research, 2021)
The methodology that critical theory adopted focuses on the notion of interdisciplinarity as the innovative path for the exchange of arguments among all sciences. The critique that the article deploys on the epistemological tendencies of late modernity suggests that the main distinction between modern epistemology and the critical theorists lies in their understanding of normativity and rationality. Such a critique can be characterized as the ‘battle’ of modern epistemology for or against the scientifically, socially, and politically rational.